How I Do It : Bilateral Cleft Lip Repair - Sudjatmiko, Gentur; Pribadi, Sweety (Jurnal Plastik Rekonstruksi, 2013)
Several techniques have evolved to achieve better outcomes in bilateral cleft lip repair. The techniques performed should overcome the challenge presented in bilateral cleft lip, such as protrusion of premaxilla, the short columella, the wide gap, minimal dry mucosa in prolabium also the low socioeconomic level that typically presented in cleft patient. Considering the challenges mentioned above, a proper design and precise technique should be defined. We proposed a design and technique with promising results, which involves: 1) The precision of the design, the adjustable point of the design to modify lateral flap will provide adequate thickness of vermillion to create tubercle as well as to provide adequate tissue for nasal floor. 2) The possibility to approximate the orbicularis oris muscle although the premaxilla is protruded. It is beneficial and cost-effective for the patients who cannot afford preoperative orthodontic treatment. 3) The suggestion to not worry about the immediate postoperative result as it will evolve to a satisfactory result. 4) The use of non-absorbable nylon 5.0 and 6.0 for the whole layers will overcome tension and reduce cost.